(3efGgL GdacQ heHGgL GdYHQs - (3eMeO Hf EHQGgje Hf jMji Hf Ydj GdCfUGQj GdcJHj, LeGd GdOjf, GdeYQha H` GdhWhGW , J (B718 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eJbf eG UfY heHOY eG Ndb GdPi Nda GdfHGJ hbSeI GdMLe hHYO agPG Gdaf GdQGHY ef Gdafhf GdPi OGaY GdYbd ai JOhjfgG ghi GdfaS hTGjY HjGV GdWQS s
(3BNQgG (B:s
(3hSbjfGg hjdRe JRHdg ceG gh eHjf HHGbi GdJRHjd s
(3jTJed Ydi GLRGA hCbSGe efgGs
(3hgPG gh Gdaf GdQGHY ai GdfHGJs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B42s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs